ANTIMALARIAL MEDICINAL PLANTS USED BY TRADITIONAL HEALERS IN BENGKULU PROVINCE OF INDONESIA - Dian Susanti; Aditya Dwi Permana Putra; Devi Safrina; Nur Rahmawati Wijaya; M Bakti Samsu Adi; Rohmat Mujahid; Rizal Maarif Rukmana; Dyah Subositi; Sari Haryanti; Usman Siswanto; Yuli Widiyastuti (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlights - This research provides information on the use of medicinal plants for treating malaria among ethnic groups in Bengkulu Province. - This research was part of RISTOJA (Research on Medicinal Plants), national research conducted by the Ministry of Health of the Republic of Indonesia. - Several compounds found in medicinal plants used by traditional healers in the Bengkulu Province have been scientifically proven to be effective as antimalarial medication.